Stress-deformation characteristics of the machining system and possibilities of printing the formability potential of a material - Vujović, Vlado (Journal of Production Engineering, 1984)
The paper starts from the fact that metallic materials have a great potential of deformability and that the main problem in exploiting this potential is the formulation of a suitable machining system that allows the manifestation of the desired deformability by the machining conditions. This allows a very wide range of possibilities in the design of the machining system. The total stress tensor is calculated on the deviatoric part and the real part, interpreting geometrically the different possibilities of formation of the local strain by the deviatoric part, and then analyzing the influence of the addition of the real tensor of different size. The stress tensor and the deformation components play a crucial role in the formation and development of cracks in the material, so they are decisive for the limit of deformability. The paper mainly analyzes the influence of the stress components, but the manifestation of deformability. However, the influence of the deformation components and their relationship to the stress components should be particularly analyzed, which is probably beyond the possible scope of this paper.